2012
DOI: 10.4239/wjd.v3.i8.149
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1* alleles and genetic susceptibility to type 1 diabetes mellitus

Abstract: AIM:To determine human leukocyte antigen (HLA)-DQB1 allele association with susceptibility to type 1 diabetes (T1D) and to clinical and laboratory findings. METHODS:This study was conducted on 85 unrelated Egyptian children with T1D recruited consecutively from the Pediatric Diabetes Endocrinology outpatients Clinic; Mansoura University Children's Hospital, Egypt. Patient mean follow up period was 2.5 years. Patients were subdivided according to level of HbA1c (optimal/suboptimal control < 8.5% and poor contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Despite the strong evidence for a genetic predisposition towards T1D, epidemiological data indicating the involvement of additional environmental factor(s) in disease etiology remain compelling. The human leukocyte antigen (HLA) genotype, the dominant genetic marker for T1D, is found in only 20–30% of T1D patients, and in only 50% of patients diagnosed in early childhood [ 1 , 2 ]. In addition, less than half of HLA-susceptible monozygotic twins both develop T1D [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strong evidence for a genetic predisposition towards T1D, epidemiological data indicating the involvement of additional environmental factor(s) in disease etiology remain compelling. The human leukocyte antigen (HLA) genotype, the dominant genetic marker for T1D, is found in only 20–30% of T1D patients, and in only 50% of patients diagnosed in early childhood [ 1 , 2 ]. In addition, less than half of HLA-susceptible monozygotic twins both develop T1D [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence has shown that genetic factors play important roles in the development of type 1 diabetes mellitus. However, identification of specific responsible genes and their variants has had limited success.…”
Section: Introductionmentioning
confidence: 99%
“…The association of specific HLA-DQB1 alleles and genotypes with T1D susceptibility/protection depends on the ethnicity and racial background of each population. For example, in Caucasians, T1D is positively associated with DQB1*0201 and DQB1*0302 while in Japanese, it is associated with DQB1*0401 and DQB1*0303 [156].…”
Section: Hla and Autoimmune Diseasesmentioning
confidence: 99%